Pengaruh Komik Penuntun Praktikum Biologi Kelas XI IPA Terhadap Kemampuan Psikomotorik Siswa SMA Negeri 2 Sukoharjo Semester Genap Tahun Ajaran 2015/2016 - Dianing Tyas, Dewi; , Dr. Sofyan Anif, M.Si (2016)
This research aims to know the effectiveness of the use of methods of comics in the use of Biological practical guiding of psychomotor ability SMAN 2 Sukoharjo academic year 2015/2016. This research method using True Experimental Design, with the form Post Test Only Control Group Design. The population in this research is the whole grade XI. Sampling used in this study was a random sampling technique, with class XI MIPA 1 and class XI MIPA 2 as class experiments, while the class of XI MIPA 3 as a class controls. Data obtained by the value of the skills and values of post-test and documentation, analysis of the data used is One Way Anova with a prerequisite test normality and its homogeneity test. Results the data obtained did not meet the prerequisites then test data analysis using test Kruskall-Walis. The value of the skills and values of post-test obtained probability values is 0.000 lower than 0.05. Then the decision taken is H0 is rejected, so it was concluded that there is an influence the guiding comic practeical biology toward psychomotor ability when implement the biology practical.